The predictive value of monocyte count to high-density lipoprotein cholesterol ratio combined with left atrial diameter for post-radiofrequency ablation recurrence of paroxysmal atrial fibrillation in patients - Yu Lei; Lijun Hu (Journal of Cardiothoracic Surgery)
Abstract Background Paroxysmal atrial fibrillation (PAF) usually recurs after radiofrequency ablation (RFA). This study probed the predictive value of monocyte count to high-density lipoprotein cholesterol (HDL-C) ratio (MHR) with left atrial diameter (LAD) for post-RFA recurrence in PFA patients. Methods Totally 210 RFA-treated PAF patients were selected and assigned into Recurrence and Non-Recurrence groups, with clinical baseline data recorded. Preoperative HDL-C, hypersensitive C-reactive protein, interleukin-6, tumor necrosis factor alpha, brain natriuretic peptide, low-density lipoprotein cholesterol, total cholesterol, and total cholesterol were determined. Monocyte count and MHR were examined. The effects of preoperative MHR and LAD on post-RFA PAF recurrence was analyzed by COX regression analysis. Patients were arranged into high and low MHR and high and low LAD groups. The recurrence of PAF patients with different preoperative MHR and LAD within 12 month was analyzed by Kaplan-Meier (KM) analysis. The predictive value of preoperative MHR, LAD, and their combination for post-RFA recurrence in PAF patients was analyzed. Results MHR and LAD were independent risk factors for post-RFA recurrence in PAF patients. KM curve shift left in the high MHR and LAD groups versus the low MHR and LAD groups. MHR and LAD could help predict post-RFA recurrence in PAF patients, and the combined predictive value of MHR and LAD was greater than that of either factor alone. Conclusion MHR and LAD are independent risk factors for post-RFA PAF recurrence, and can help predict post-RFA recurrence in PAF patients, with their combined predictive value higher than that of each factor individually.